Brazilian oral pathology: a retrospective survey of 245 cases from a Surgical Pathology Hospital Laboratory - Nascimento, Juliana Souza; Takahama Jr, Ademar; Pires, Fábio Ramôa; Barros, Eleni Maria Viana de Brandão; Azevedo, Rebeca Souza (Brazilian Dental Science, 2016)
Objective: The aim of this study was to determine the range of oral histopathological diagnoses in a Brazilian survey obtained from a surgical pathology hospital laboratory. Material and Methods: A retrospective cross-sectional study was performed, and all histological slides from the oral and maxillofacial region during a 14-year period were reviewed. The materials were grouped into five major diagnostic categories, and age and sex were specified. Results: A total of 769 samples were collected and submitted for histopathological analysis. There were 245 oral cases, which were divided into 48 different diagnoses. There was no sex predilection, and the mean age was about 44 years old. Proliferative non-neoplastic lesions (43.2%) and malignant neoplasms (26.5%) comprised the main two groups of diagnoses. Conclusion: The malignant prevalence observed in this Brazilian sample may be due to the nature of the population or, most probably, to the nature of the source, a referral hospital center in the city.